Introduction to Biochemistry: Protein Structure and Enzyme Basics - Daniel Eskenazi; David Acosta (Association of American Medical Colleges, 2010)
Abstract Introduction The purpose of this learner-directed, stand-alone tutorial is to teach learners how basic science building blocks relate to clinical scenarios in the field of biochemistry. The goal is for them to retain information regarding protein structure and enzyme basics and understand how it ultimately relates to physiology and medicine. Specifically, students will build upon basic chemical and physical principles to understand biochemistry in the context of Gibbs free energy, activation energy plots, and enzyme reaction rate analysis. Further, students will connect this knowledge clinically by relating structural changes to the disease sickle cell anemia and metabolic changes to the disease phenylketonuria. Review questions at the end of the tutorial provide the opportunity to practice drawing structures and to test their knowledge. Methods The tutorial is designed to be completed by students over one or two sessions, perhaps by dividing it up into protein structure for one session and enzyme basics for another session. Motivated students will be able to find the tutorial online as an tool to both aid in coursework and preparation for health school entrance exams. Instructors may review the materials to supplement lessons and incorporate further discussion of topics brought up in the tutorial. The slides themselves may be used as guides to expand topics or to fit the structure of existing syllabi. Results This tutorial is based on materials used in the Summer Medical & Dental Education Program (SMDEP) at the University of Washington School of Medicine over 2 years, and experienced by more than 50 students. Effectiveness was assessed via final examination containing multiple choice questions as well as short-answer questions and drawing structures; all motivated students excelled at this exam with some performing outstandingly well (> 95% score on a 50 multiple-choice, 10 short-answer question exam, covering this material and six other lessons). Student enthusiasm of the course was evaluated by questionnaire; biochemistry scored the highest of all SMDEP components in 2009. Discussion The significance of this work is that it will serve as a supplement to any undergraduate biochemistry course by providing a free, open-access, aid for students to access in preparation for their undergraduate coursework and professional school entrance exams.